Sertoli Cell-Germ Cell Interactions Within the Niche: Paracrine and Juxtacrine Molecular Communications - Hofmann, Marie-Claude; McBeath, Elena (Frontiers in Endocrinology, 2022)
During the perinatal period, male germ cell development depends on multiple biological events that combine epigenetic reprogramming, cell cycle regulation, and cell migration in a spatio-temporal manner. Sertoli cells are a major component of the spermatogonial stem cell niche and provide essential growth factors and chemokines to developing germ cells. This review focuses mainly on the activation of master regulators of the niche in Sertoli cells and their targets, as well as on novel molecular mechanisms underlying the regulation of growth and differentiation factors such as GDNF and retinoic acid by NOTCH signaling and other pathways.